PENDIDIKAN MULTIKULTURALISME DI YAYASAN KRISTEN KATHOLIK: STUDI SMK YOS SOEDARSO SIDAREJA - Riyani Pujiana; Fitri Apriani (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2018)
Multiculturalism as a concept to understand and accept differences each individual, thus if multiculturalism is not crated in a good way, it can generate conflict between groups especially in an environment that has varieties such as SMK Yos Soedarso Sidareja. The principle of variety each group will appear conflict between groups easily because of principle differences from those groups. As an effort to minimalize conflict between groups, then we must invest awareness by means of multiculturalism education to accept pluralism, equality, humanity, justice, and democracy value.